Sickness absence as a risk factor for job termination, unemployment, and disability pension among temporary and permanent employees. Issue 3 (23rd February 2006) - Virtanen, M; Kivimäki, M; Vahtera, J; Elovainio, M; Sund, R; Virtanen, P; Ferrie, J E
Abstract : Objectives: This study examined sickness absence as a risk factor for job termination, unemployment, and disability pension among temporary and permanent workers. Methods: Prospective cohort study with data on employment contract and sickness absence in 1996, job termination by 1997, and employment status in 1997 and 2000 for 19 093 temporary and 41 530 permanent public sector employees. Results: For women aged 40 years or less and for women over 40, a high sickness absence increased the risk of job termination among temporary employees (OR 1.52 (95% CI 1.36 to 1.71) and OR 1.70 (95% CI 1.36 to 2.13) respectively). High absence was not associated with job termination among men in temporary employment. Among permanent employees, high sickness absence predicted job termination among older, but not among younger employees. Temporary employees with high sickness absence were at the highest risk of immediate unemployment and unemployment three years later. Among older permanent employees, high sickness absence was associated with subsequent work disability pension. Conclusions: A high rate of sickness absenteeism increases the risk of job termination and unemployment among women in temporary public sector jobs. For permanent employees, secure employment provides protection against unemployment even in the case of high sickness absence.